Kedudukan Jaminan Syariah dalam Perbankan Syariah - Novita Indah Sulistyowati (Officium Notarium, 2022)
The growth of Islamic banking each year has an influence on the regulations that underlie the existence of Islamic banks in Indonesia. The existence of Islamic banks helps people a lot in facing the world economic competition. Therefore, the more advanced lives of the people, the more law is needed as in the provisions of sharia guarantees in sharia banking. The formulation of the problem in this study is, first, what is the position of Islamic guarantees in Islamic banking? Second, what are the provisions in Islamic banking regarding customers who default on the al-rahn contract? The research method used is normative or doctrinal with the research object of the Al-Quran and Hadith as well as laws and regulations. The approach used is the case study and doctrinal approach with primary legal materials in the form of laws and regulations, and secondary legal materials in the form of books and journal articles. The results of this study conclude that the position of sharia guarantees in Islamic banking is dependent on the contract to be made between the bank and the customer as in the DSN-MUI Fatwa hence it can be concluded that sharia guarantees in Islamic banking are not required to be carried out and arrangements regarding al-Rahn in Islamic banking if there is default is the same as the provisions of western civil law, namely through sharia auctions.Key Word: Sharia Guarantee, Islamic Banking AbstrakPertumbuhan perbankan syariah dari tahun ke tahun mempunyai pengaruh atas peraturan yang mendasari keberadaan bank syariah di Indonesia. Keberadaan bank syariah banyak membantu masyarakat dalam menghadapi persaingan ekonomi dunia. Oleh karena itu, semakin maju kehidupan masyarakat maka semakin dibutuhkan hukum sebagaimana ketentuan jaminan syariah pada perbankan syariah. Rumusan masalah pada penelitian ini, pertama, bagaimana kedudukan jaminan syariah dalam perbankan syariah? Kedua, bagaimana ketentuan dalam perbankan syariah mengenai nasabah yang wanprestasi atas akad al-rahn? Metode penelitian yang digunakan adalah normatif atau doktrinal dengan objek penelitian Al-Quran dan Hadist serta peraturan perundang-undangan. Pendekatan yang digunakan yaitu pendekatan kasus dan doktrin dengan bahan hukum primer berupa peraturan perundang-undangan, dan bahan hukum sekunder berupa buku serta jurnal. Hasil dari penelitian ini menyimpulkan bahwa kedudukan jaminan syariah dalam perbankan syariah adalah tergantung pada akad yang hendak dilakukan antara bank dan nasabah sebagaimana Fatwa DSN-MUI sehingga dapat disimpulkan bahwa jaminan syariah dalam perbankan syariah adalah tidak wajib dilaksanakan dan pengaturan mengenai Rahn pada perbankan syariah jika terjadi wanprestasi sama dengan ketentuan hukum perdata barat yaitu melalui lelang syariah.Kata-kata Kunci: Jaminan Syariah, Perbankan Syariah